Epiphytic common core bacteria in the microbiomes of co-located green (Ulva), brown (Saccharina) and red (Grateloupia, Gelidium) macroalgae - Lu, De-Chen; Wang, Feng-Qing; Amann, Rudolf I.; Teeling, Hanno; Du, Zong-Jun (Microbiome, 2023)
Background Macroalgal epiphytic microbial communities constitute a rich resource for novel enzymes and compounds, but studies so far largely focused on tag-based microbial diversity analyses or limited metagenome sequencing of single macroalgal species. Results We sampled epiphytic bacteria from specimens of Ulva sp. (green algae), Saccharina sp. (brown algae), Grateloupia sp. and Gelidium sp. (both red algae) together with seawater and sediment controls from a coastal reef in Weihai, China, during all seasons. Using 16S rRNA amplicon sequencing, we identified 14 core genera (consistently present on all macroalgae), and 14 dominant genera (consistently present on three of the macroalgae). Core genera represented ~ 0.7% of all genera, yet accounted for on average 51.1% of the bacterial abundances. Plate cultivation from all samples yielded 5,527 strains (macroalgae: 4,426) representing 1,235 species (685 potentially novel). Sequencing of selected strains yielded 820 non-redundant draft genomes (506 potentially novel), and sequencing of 23 sampled metagenomes yielded 1,619 metagenome-assembled genomes (MAGs), representing further 1,183 non-redundant genomes. 230 isolates and 153 genomes were obtained from the 28 core/dominant genera. We analyzed the genomic potential of phycosphere bacteria to degrade algal polysaccharides and to produce bioactive secondary metabolites. We predicted 4,451 polysaccharide utilization loci (PULs) and 8,810 biosynthetic gene clusters (BGCs). These were particularly prevalent in core/dominant genera. Conclusions Our metabolic annotations and analyses of MAGs and genomes provide new insights into novel species of phycosphere bacteria and their ecological niches for an improved understanding of the macroalgal phycosphere microbiome. DnRc39z963CYrL7RdN5UNd Video Abstract